CLINICAL PROFILE AND OUTCOME IN A PAEDIATRIC INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL IN PAKISTAN - Khan, Qamar uz Zaman; Basheer, Faisal; Nayyar, Zameer Ahmad; Butt, Aroosa Ishtiaq (Pakistan Armed Forces Medical Journal, 2020)
Objective: To study the characteristics of the patients admitted in paediatric intensive care unit of Pak Emirates Military Hospital Rawalpindi and record their outcomes in terms of mortality and discharge.Study Design: Prospective observational study.Place and Duration of Study: Paediatric Intensive Care Unit, Pak Emirates Military Hospital Rawalpindi, from Sep 2017 to Mar 2017.Methodology: All consecutive paediatric intensive care unit admissions were prospectively studied till discharge or death. The following data were collected prospectively: age; sex; diagnosis at the time of admission; elective/ emergency status; operative status; the need for mechanical ventilation; paediatric intensive care unit length of stay (LOS) and the outcome in terms of mortality and discharge. Descriptive statistics were calculated for all variables.Results: Among 531 children admitted in 6 months, 308 (58%) were boys and 223 (42%) were girls. The average length of paediatric intensive care unit stay was 4.11 ± 1.88. Mortality rate in our unit was 26.6%. The majority died due to respiratory diseases and LRTI (25.5%). The median age was 8 months (range: 1 day old to 13 years) and 59.3% admissions were less than 1 year of age that also included neonates. One hundred and forty-one children (23%) received mechanical ventilation, while around 30% received vasoactive drugs.Conclusion: The clinical profile and outcomes in paediatric intensive care unit at Pak Emirates Military Hospital Rawalpindi appears to be almost at par with minor differences in certain aspects with the other paediatric intensive care units in Pakistan.